(untitled) (Research, Society and Development, 2022)
Smallpox was considered eradicated from the face of the earth. Monkeypox was discovered about 60 years ago and remains under surveillance in the health sector. It is a zoonotic infection that remains endemic in Central and West Africa in animal reservoirs, with increasing numbers of human cases and some outbreaks reported. Known by the name of Monkeypox, it is caused by a double-stranded DNA virus that belongs to the genus Orthopoxvirus in the family Poxviridae. Lymphadenopathy was a prominent feature of monkeypox disease. The main routes of infection are largely by respiratory droplet or percutaneous or mucosal contact. The time of exposure and onset of fever varies from 10 to 14 days, and the interval between exposure and the appearance of the rash varies from 12 to 16 days. Fever is accompanied by headache, myalgia, back pain, malaise and prostration, in addition to a rash 1 to 3 days after the onset of fever. The interval between fever and rash. The aim of this study is to review through the scientific literature the importance of an integral approach to the clinical and epidemiological aspects of Monkeypox, monkeypox. There are no specific treatments for monkeypox virus infection. Monkeypox symptoms usually resolve spontaneously. It is advised to avoid touching any injury to the mouth or eyes. Smallpox vaccination helps prevent or alleviate monkeypox disease.